Integrasi Nilai Religius dan Sekuler Pada Lembaga Pesantren, Madrasah dan Sekolah Islam di Indonesia - Wiwid Hadi Sumitro; Abu Anwar; Helmiati (Universitas Nahdlatul Ulama Surabaya, 2020)
The world of education is a very dynamic learning system, always moving according to developments and needs. As we have experienced, Indonesian education has experienced major obstacles, especially the dichotomy problem of education, between religion and the general public. In accordance with the times that Islam and science cannot follow integrated Islamic boarding schools, madrasas and Islamic schools, because the two sciences are complementary. By using the library research method the writer wants to find integration or a close relationship with these two values ​​in Islamic boarding schools, madrasas and integrated Islamic schools in this new normal era. So it is found that several findings these institutions have the same goal in grounding education both Islam and the general public, but different in the forms and models applied in the field.